Vegetation changes due to the game exclusion and the overpopulated game in the Budai-mountain’s dolomite grassland - Baráth, Norbert; Bartha, Sándor; Házi, Judit; Wichmann, Barna; Penksza, Károly (Animal welfare, Ethology and Housing Systems (AWETH), 2012)
In the present work two rocky grassland - within National Protection Area of Buda – were examined according to game pressure (grazing, trampling) on them. A fence was built by the national park to excluse the non-native game from the Szénások European Diploma Area. Coenological examination were performed in case of Kutya-mountain (inside the fence) and Meszes-mountain (outside the fence) between 2008 and 2011 by the modified method of Braun-Blanquet (1964). Mikrocoenological samples (Juhász-Nagy 1980) were made also. Our goal was to verify the importance and positive effect of nature protection intervention. The results show that values in the sixth of nature protection intervention exceed the initial state values in Kutyamountain. Coverage ratios of valuable species – according to classification of social behavior and natural protection categories of species – increased in parallel with decrease of dominant pioneer species values. The classification showed difference between the sampling years of 2005 and 2010-2011. Parallel the study of game exclusion, effect of moufflon (Ovis musimon) to the rocky grasslands was examined. During comparsion all of nature conservation analysis resulted less favorable results in case of Meszes-mountain habitat than results from Kutya-mountain habitat (nature conservation value, diversity and mikrocoenological results).